(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to explore existing approaches for capacity building and professional development among nursing educators and to identify their needs and expectations regarding training programs. Methods: A qualitative research design was employed to examine nursing educators’ perspectives on professional development and training activities. Data were collected through semi-structured interviews with 11 nursing faculty members from universities and colleges of medicine and pharmacy in Northern Vietnam, conducted between March 2023 and June 2024. Results: Findings indicate that nursing educators actively engage in professional workshops, continuing education courses, and utilize online academic resources to update their teaching knowledge and skills. However, many current training programs remain overly theoretical, lack practical relevance, and fall short of meeting international standards. Identified urgent needs include regularly updated training content with a strong focus on technology integration in teaching and scientific research, enhanced access to international training and academic exchange opportunities, and the establishment of sustainable financial and institutional support mechanisms for long-term professional development. Conclusion: The study sheds light on the current status and developmental needs of nursing educators in Northern Vietnam. It recommends the development of structured, continuous professional training programs that incorporate both material and non-material incentives to promote proactive engagement. These recommendations serve as a crucial foundation for formulating strategic policies to improve the quality of nursing educators, thereby contributing to more effective educational outcomes and addressing healthcare workforce demands in the context of global integration.